The cement of civil society studying networks in localities - Diani, Mario 1957- (Cambridge studies in contentious politics, 2015)
Civil society is frequently conceived as a field of multiple organizations, committed to highly diverse causes and interests. When studied empirically, however, its properties are often reduced to the sum of the traits and attitudes of the individuals or groups that are populating it. This book shows how to move from an 'aggregative' to a relational view of civil society. Drawing upon field work on citizens' organizations in two British cities, this book combines network analysis and social movement theories to show how to represent civil society as a system of relations between multiple actors. 'Modes of coordination' enables us to identify different logics of collective action within the same local settings. The book exposes the weakness of rigid dichotomies, separating the voluntary sector from social movements, 'civic' activism oriented to service delivery from 'un-civic' protest, grassroots activism external to institutions from formal, professionalized organizations integrated within the 'system'